Harnessing the microbiota for therapeutic purposes. Issue 6 (30th December 2019) - Liwinski, Timur; Elinav, Eran
Abstract : The myriads of microorganisms colonizing the human host (microbiome) affect virtually every aspect of its physiology in health and disease. The past decade witnessed unprecedented advances in microbiome research. The field rapidly transitioned from descriptive studies to deep mechanistic insights into host‐microbiome interactions. This offers the opportunity for microbiome‐targeted therapeutic manipulation. Currently, several strategies of microbiome‐targeted interventions are intensively explored. Best evidence from human randomized clinical trials is available for fecal microbiota transplantation (FMT). However, patient eligibility as well as long‐term efficacy and safety are not sufficiently defined. Therefore, there is currently no officially approved indication for FMT. Probiotics (live microorganisms) have long been discussed as a means to aid human health but have yielded varying results. Emerging techniques utilizing microbiota‐targeted diets, small microbial molecules, recombinant bacteriophages, and precise control of strain abundance recently yielded promising results but require further investigation. The rapid technological progress of "omics" tools spurs advances in personalized medicine. Understanding and integration of interindividual microbiome variability holds potential to promote personalized preventive and therapeutic approaches. Emerging evidence points towards the microbiome as an important player having an impact on transplantation outcomes. Microbiome‐targeted interventions have potential to aid against the many challenges faced by transplant recipients. Abstract : In this review, the authors summarize recent progress in translating microbiome research into therapeutic interventions with emphasis on transplantation medicine.